Asuhan Keperawatan Pada Ny.T Dengan Gangguan Sistem Kardiovaskular: Hipertensi Di Ruang Dahlia RSUD dr. Soeselo Kabupaten Tegal - Ummu Hani; Esti Nur Janah; Wawan Hediyanto (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Hypertension is one of the most common cardiovascular diseases and is most common in society. Hypertension is now a major problem for all of us, not only in Indonesia but in the world, because hypertension is a risk factor for heart disease, kidney failure, diabetes and stroke (Indonesian Ministry of Health, 2019). Data from the World Health Organization (WHO) in 2018 shows that around 1.13 billion people in the world have hypertension, meaning that 1 in 3 people in the world are diagnosed with hypertension. The number of people with hypertension continues to increase every year, it is estimated that by 2025 there will be 1.5 billion people affected by hypertension and it is estimated that every year 10.44 million people die due to hypertension and its complications (Ministry of Health, 2019). Based on Riskesdas 2018, the prevalence of hypertension based on measurement results in the population aged 18 years was 34.1%, the highest in South Kalimantan (44.1%), while the lowest was in Papua (22.2%). Hypertension occurred in the age group 31-44 years (31.6%), age 45-54 years (45.3%), age 55-64 years (55.2%). From the prevalence of hypertension of 34.1%, it is known that 8.8% were diagnosed with hypertension and 13.3% of people diagnosed with hypertension did not take medication and 32.3% did not regularly take medication. This shows that the majority of hypertension sufferers do not know that they have hypertension and therefore do not receive treatment (Ministry of Health, 2019).